Why did You do that to Me?: a Systematic Review of Cyberbullying Impact on Mental Health and Suicide Among Adolescents - Dinar Rizqi Perwitasari; Emi Wuri Wuryaningsih (NurseLine Journal, 2022)
With the new implementation of distance learning, adolescents have more time to access the internet. Lack of surveillance from parental figures and developing senses of mental stability make adolescents susceptible to the negative influence of the internet such as cyberbullying. This systematic literature review aims to examine the incidence of cyberbullying and its effect on the risk of mental health disorders and suicide among adolescents during the COVID-19 pandemic. A total of 10 cross-sectional studies were sorted out from major electronic journal databases: PubMed, Science Direct, BMC, Sage Journal, and Google Scholar using the following search term combinations: “adolescents” “cyberbullying” “suicide” “depression”. The range for adolescents age was 11-18 years. These studies identified and examined general internet use, the experience of cyberbullying, effects on mental health disorder, and risk of suicide published from January 2020 to July 2021. Cyber victimization was positively associated with stress, suicidal ideation, and avoidance which is also a significant predictor of self-harm. Adolescents who experienced cyberbullying were 2-3.14 times more likely to report experiencing suicidal ideations. Suicidal attempts were significantly 2.14 times higher on adolescents who have cyberbullying experience. Previously victimized adolescents have a 15.5% higher chance of being cyberbullied. Internet usage and addiction have direct effects on mediating cyber victimization and adolescents’ psychological symptoms. This study has given broader insight into how cyberbullying can affect mental health in adolescents and identify the gaps for further longitudinal research on cyberbullying among adolescents.